2021
DOI: 10.30892/gtg.38436-770
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education and Training Towards Global Competitiveness and Human Development in Indonesia

Abstract: This research explains about Indonesian labor competitiveness from perspective of the 5th pillar GCI (education and training). The purpose is to (1) measure the readiness of Indonesian labor at the ASEAN level and (2) ana-lyzed relationship between GCI and HDI. This research was using descriptive and inferential analysis. The re-sults show Indonesia is in fourth place in ASEAN. Coefficient correlation between the 5th pillar of CGI and HDI is 0.874. This explain the quality of human development is strongly rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Depending on the perspectives of the specialists in the field of human development and competitiveness, 60% approved the positive relationship between innovative technology and improving HDI, while 10% argued for several reasons, such as the rapid technological developments which can vastly contribute to improving areas of human development. Moreover, this finding accords with Deffinika et al (2021), who found that the development of innovative technological systems according to the concept of institutional theory has become more participatory and integrative, which has served to significantly improve society's quality of life and the enhancement of human development.…”
Section: Demographysupporting
confidence: 79%
See 4 more Smart Citations
“…Depending on the perspectives of the specialists in the field of human development and competitiveness, 60% approved the positive relationship between innovative technology and improving HDI, while 10% argued for several reasons, such as the rapid technological developments which can vastly contribute to improving areas of human development. Moreover, this finding accords with Deffinika et al (2021), who found that the development of innovative technological systems according to the concept of institutional theory has become more participatory and integrative, which has served to significantly improve society's quality of life and the enhancement of human development.…”
Section: Demographysupporting
confidence: 79%
“…The UAE community is relatively well-educated, with the majority of males having completed secondary school; however, UAE females are more likely to seek higher education. UAE expats, on the other hand, have a more limited educational background, with the majority of men only receiving an elementary education (Deffinika et al, 2021).…”
Section: Uae Demographic Trendsmentioning
confidence: 99%
See 3 more Smart Citations